The effect of nutritional status on post-operative outcomes in pediatric otolaryngology-head and neck surgery. (November 2021) - Luttrell, Jordan; Spence, Matthew; Al-Zubeidi, Hiba; Herr, Michael J.; Mamidala, Madhu; Sheyn, Anthony
Abstract: Introduction: Nutritional status can affect surgical patients in terms of stress response, healing time, and outcomes. Several abnormalities are known to have a high prevalence in the general population such as vitamin D deficiency (VDD) and subclinical hypothyroidism. We hypothesized that there will be elevated rates of nutritional deficiencies in preoperative patients which may adversely affect postoperative outcomes following pediatric otolaryngology surgery. Methods: IRB approval was obtained for a cross-sectional cohort study. Consecutive patients underwent nutritional evaluation when being scheduled for surgery including TSH, albumin and vitamin D. Demographic data, supplementation, and early complication rates were collected. Results: 125 patients were included in the final cohort with adequate demographic distribution. Based on anthropometric data, 12% of our cohort was found to be undernourished, and 40% of our cohort with elevated BMI. However, there was no relationship found between Z-scores and complications. VDD was noted in 83/125 (66.4%) patients. Our cohort had increased rates of VDD in patients with elevated BMI and African American ethnicity. Thyroid hormone abnormalities were present in 12 patients. Mean serum albumin level was 4.29 in our cohort all within normal range. We did find increased risk of postoperative complications in patients with previously diagnosed comorbidities. (p=0.006). Conclusion: There is no current recommendation or consensus for nutritional assessment in preoperative pediatric patients. Our study did not show statistically significant correlation with z-scores, low vitamin D levels with supplementation, albumin, or TSH to postoperative complications. However, our patient cohort had higher than average rates of VDD compared to the many studies of the general pediatric population and significant negative correlation between vitamin D levels and z-scores. By early preoperative identification of VDD and supplementation with calciferol, we found no significant difference in complication rates in patients based on their initial vitamin D status. We suggest screening preoperative patients using z-score calculations and vitamin D levels based on individual patient risk factors including atrisk patient populations such as African American children, and obese children.